PRODUCTIVE QUALITIES OF PIGS OF RED BILOPOYASOY AND LARGE WHITE BREEDS AT DIFFERENT METHODS OF BREEDING - Мангура, Л. П. (Scientific Progress & Innovations, 2014)
The results of productive qualites of red white belt (RWB) and large white (LW) pigs’ breeds by reciprocal crossbreeding have been shown. It has been established that the most polycarpic (10.91 piglets) have been revealed the sows of LW breed be thoroughbred breeding. By crossbreeding more polycarpic (10,82 piglets) have been revealed combinations LW х LWB. By this combination has been revealed the live weight piglets’ nest by taking away after 60 days. Live weight of every weanling has been the highest (17,61 kg) by thoroughbred red white belt piglets. Crossbreeding of the sow LW with the boars LWB has been conducive more intensive for growth of crossbreeded youngsters by the less food consumption on every kg of growth.